Large Polyhedral Oligomeric Silsesquioxane Cages: The Isolation of Functionalized POSS with an Unprecedented Si18O27 Core. Issue 6 (3rd December 2020) - Laird, Mathilde; Herrmann, Niklas; Ramsahye, Naseem; Totée, Cédric; Carcel, Carole; Unno, Masafumi; Bartlett, John R.; Wong Chi Man, Michel
Abstract: The synthesis of organo‐functionalized polyhedral oligomeric silsesquioxanes (POSS, (R‐SiO1.5 ) n, T n ) is an area of significant activity. To date, T14 is the largest such cage synthesized and isolated as a single isomer. Herein, we report an unprecedented, single‐isomer styryl‐functionalized T18 POSS. Unambiguously identified among nine possible isomers by multinuclear solution NMR ( 1 H, 13 C, and 29 Si), MALDI‐MS, FTIR, and computational studies, this is the largest single‐isomer functionalized T n compound isolated to date. A ring‐strain model was developed to correlate the 29 Si resonances with the number of 6‐, 5‐, and/or 4‐Si‐atom rings that each non‐equivalent Si atom is part of. The model successfully predicts the speciation of non‐equivalent Si atoms in other families of T n compounds, demonstrating its general applicability for assigning 29 Si resonances to Si atoms in cage silsesquioxanes and providing a useful tool for predicting Si‐atom environments. Abstract : A POSS cage with a Si18 O27 core is described. In contrast to previous large POSS cages ( n >16), our synthesis afforded a single isomeric form, unambiguously identified from among the nine possible isomers by NMR. This is the largest Tn compound isolated as a single isomer. A new ring strain model is described that correlates the chemical shifts of non‐equivalent 29 Si NMR signals in POSS.